Honey Bees Can Taste Amino and Fatty Acids in Pollen, but Not Sterols - Ruedenauer, Fabian A.; Biewer, Niklas W.; Nebauer, Carmen A.; Scheiner, Maximilian; Spaethe, Johannes; Leonhardt, Sara D. (Frontiers in Ecology and Evolution, 2021)
The nutritional composition of food is often complex as resources contain a plethora of different chemical compounds, some of them more, some less meaningful to consumers. Plant pollen, a major food source for bees, is of particular importance as it comprises nearly all macro- and micronutrients required by bees for successful development and reproduction. However, perceiving and evaluating all nutrients may be tedious and impair quick foraging decisions. It is therefore likely that nutrient perception is restricted to specific nutrients or nutrient groups. To better understand the role of taste in pollen quality assessment by bees we investigated nutrient perception in the Western honey bee, Apis mellifera. We tested if the bees were able to perceive concentration differences in amino acids, fatty acids and sterols, three highly important nutrient groups in pollen, via antennal reception. By means of proboscis extension response (PER) experiments with chemotactile stimulation, we could show that honey bees can distinguish between pollen differing in amino and fatty acid concentration, but not in sterols. Bees were also not able to perceive sterols when presented alone. Our finding suggests that assessment of pollen protein and lipid content is prioritized over sterol content.